Desenvolvimento das habilidades visuoespaciais na síndrome de Turner - Rafael Nunes dos Santos (2022)
Turner syndrome (TS) is a genetic disorder characterized by the total or partial absence of the X chromosome. TS is typically associated with impairments in physical, physiological, and cognitive health. The cognitive characteristics of TS typically involve the presence of preserved verbal skills and deficits in visuospatial skills, non-verbal memory, attention, executive function, motor and social skills. Visuospatial deficits are the most described in the literature, with a large number of studies indicating the performance of TS as consistently inferior in tests that assess skills associated with the visuospatial domain. Despite the volume of studies, it is not known for sure which components of the visuospatial domain improve throughout development and which remain compromised in individuals with TS. Twenty-two students with TS, aged between 7 and 17 years old, participated in this study. Participants with TS were compared among themselves, in different age groups and with a control group of students without TS (n=60). The control group (CG) was carefully matched to the clinical groups taking into account chronological age, years of schooling and intelligence. All participants had their visuoconstructive skills, visuospatial memory and visuospatial planning assessed using the Rey Complex Figure test. The aim of this study was to assess in a broader way the differences between the performance of TS students in relation to the CG and to explore in which visual-spatial aspects evaluated differences are observed considering different stages of development. An alternative way of interpreting the Rey Complex Figure, called Boston Qualitative Scoring System (BQSS) was used. Part of the results were in agreement with the literature, indicating a lower general performance of students with TS in the conventional interpretation of Rey's Figure. Unpublished results were found from the BQSS, showing that age has an impact on visuoconstructive development in TS, with superior performances of older students over younger TS in measures that assess the presence and placement of graphoelements in the copying stage. However, no progression was observed in the performance of the TS in terms of precision in the reproductions of the elements (accuracy), indicating that not all aspects evaluated in the BQSS for visuoconstructive skills are significantly influenced by age in the TS. The results also showed that there are changes in the pattern of visuoconstructive difficulties and visuospatial memory presented by TS in relation to CG. Our findings contribute to a better understanding of the visuospatial differences between individuals with and without TS, and how such skills develop in this syndrome.